Factors associated with persistent pain after childbirth: a narrative review. (March 2020) - Komatsu, Ryu; Ando, Kazuo; Flood, Pamela D.
Summary: A systematic literature search was performed to identify studies that reported risk factors for persistent pain after childbirth. Many studies have sought to identify risk factors for post-delivery pain in different populations, using different methodologies and different outcome variables. Studies of several different but interrelated post-partum pain syndromes have been conducted. Factors strongly and specifically associated with persistent incisional scar pain after Caesarean delivery include a coexisting persistent pain problem in another part of the body and severe acute postoperative pain. For persistent vaginal and perineal pain, operative vaginal delivery and the magnitude of perineal trauma have been consistently linked. History of pregnancy-related and pre-pregnancy back pain and heavier body weight are robust risk factors for persistent back pain after pregnancy. Unfortunately, limitations, particularly small samples and lack of a priori sample size calculation designed to detect specific effect sizes for risk of persistent pain outcomes, preclude definitive conclusions about many other predictors and the strength of outcome associations. In future studies, assessments of specific phenotypes using a rigorous analysis with appropriate predetermined sample sizes and validated instruments are needed to allow elucidation of stronger and reliable associations. Interventional studies targeting the most robustly associated, modifiable risk factors, such as acute post-partum pain, may lead to solutions for the prevention and treatment of these common problems that impact a large population.